2012
DOI: 10.1364/oe.20.020800
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence from atmospheric aerosols observed with a multi-channel lidar spectrometer

Abstract: A lidar for measuring fluorescence from atmospheric aerosols was constructed with a third harmonic Nd:YAG laser, a 1-m diameter telescope, and a 32-channel time-resolved photon-counting spectrometer system. Fluorescence spectrum and vertical distribution of fluorescent aerosols in the lower atmosphere were observed during the nighttime with excitation at 355 nm. Relatively strong broad fluorescence was observed from Asian dust and air-pollution aerosols transported from urban and industrial areas. Rough estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…However, the integrated UV-LIF spectra, which merge all the divinity of individual spectra, provide spectral profiles similar to those obtained by florescence LIDAR or a fluorescence detection system based on collected samples [57,94,15,7,51,99]. The data from integrated UV-LIF spectra should help in the evaluation and development of LIDAR systems, as well as point detection systems based on the fluorescence properties of collected particle on a substrate or filter [72,79].…”
Section: Fluorescence Spectra From Atmospheric Aerosol Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the integrated UV-LIF spectra, which merge all the divinity of individual spectra, provide spectral profiles similar to those obtained by florescence LIDAR or a fluorescence detection system based on collected samples [57,94,15,7,51,99]. The data from integrated UV-LIF spectra should help in the evaluation and development of LIDAR systems, as well as point detection systems based on the fluorescence properties of collected particle on a substrate or filter [72,79].…”
Section: Fluorescence Spectra From Atmospheric Aerosol Particlesmentioning
confidence: 99%
“…A number of rudimentary measurements of the fluorescence excitation and emission matrix (EEM) spectra of a variety of samples aimed at characterizing atmospheric OC aerosols have been reported. These fluorescence signatures include (a) integrated signatures from particles or water-soluble extracts of atmospheric aerosol particles/droplets collected on filters or substrates (e.g., [17,49,60,90]); (b) integrated signatures from a plume of atmospheric aerosol particles measured by fluorescence light detection and ranging (LIDAR) (e.g., [57,94,15,7,51,99,22,43,56,102]); and (c) signatures from individual single aerosol particles drawn into fluorescence point sensors (e.g., [78,79,63,64,68,71,24,25,26,34,101,100]). The integrated fluorescence spectra obtained from a group of aerosol particles, or the partial extracts from them, provide some information about the compositions of the particles in (a) and (b), but it is far from what we can get from the fluorescence spectra measured from individual single aerosol particles in (c).…”
Section: Introductionmentioning
confidence: 99%
“…The system should become very shortly part of the MPLNET (Micro Pulse Lidar Network, http://mplnet.gsfc.nasa.gov/) network. The MPL system is a compact, eye-safe lidar designed for full-time unattended operation (Spinhirne, 1993;Campbell et al, 2002;Flynn et al, 2007;Huang et al, 2010). It uses a pulsed solid-state laser emitting low laser pulse energy (∼ 6µJ) at a high pulse rate (2500 Hz) and a co-axial "transceiver" design with a telescope shared by both transmit and receive optics.…”
Section: The Barcelona Micro Pulse Lidar (Mpl)mentioning
confidence: 99%
“…Noh et al (2013b) reported on the vertical distribution of the same pollen event observed with lidar and on the dependency of its diurnal variations upon the meteorological conditions (temperature, relative humidity, and wind speed). Sugimoto et al (2012) developed a lidar spectrometer system with high spectral resolution which showed promising results for investigating the vertical structure of biological particles.…”
mentioning
confidence: 99%
“…Haze days caused by anthropogenic particles from Asian continents also affect airborne microbial abundance and endotoxin levels (Wei et al, 2016). Some studies demonstrated that Asian dust events, including natural and anthropogenic particles, cause vertical mixture of bioaerosols in downwind areas, such as Japan (Huang et al, 2015b;Sugimoto et al, 2012;Maki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%